Chronic myeloid leukemia in lymphoid blast crisis with extramedullary CNS infiltration in a pediatric patient: A case report (Panacea Journal of Medical Sciences, 2024)
Chronic Myeloid Leukemia (CML) is a myeloproliferative disorder, characterized by BCR-ABL1 fusion resulting from t(9;22)(q34;q11) translocation. It constitutes 2% of all leukemia cases in children younger than 15 years. CML-Blast crisis (CML-BC) with extramedullary CNS involvement is a rare serious complication of CML with a poor prognosis.Lymphoid BC in CML is seen in 30% of cases.We present a case of an 8-year-old girl diagnosed with CML one year prior to presentation, who now presented with lymphoid BC with central nervous system (CNS) involvement.